Biomonitoring of organophosphate exposure of pesticide sprayers and comparison of exposure levels with other population groups in Thessaly (Greece). Issue 2 (1st November 2013) - Koureas, Michalis; Tsakalof, Andreas; Tzatzarakis, Manolis; Vakonaki, Elena; Tsatsakis, Aristidis; Hadjichristodoulou, Christos
Abstract : Objectives: To evaluate the exposure of different population groups in Thessaly (Greece) to organophosphate pesticides (OPs) and investigate the dependence of exposure levels on pesticide application practices, personal protective and hygienic measures taken. Methods: For the exposure assessment, four dialkyl phosphate (DAP) metabolites of organophosphate pesticides were quantified in spot urine samples of 77 pesticide sprayers, 75 residents of the studied agricultural area non-involved in agricultural activities and 112 urban residents who served as a control group. Structured questionnaires were used to record demographic characteristics, pesticide application parameters and protective measures taken. Univariate and multivariate analysis of the obtained cross-sectional data was performed to identify potential risk factors associated with biomarker levels. Results: It was found that total DAP median level in the sprayers' group was 24.9 μg/g creatinine (IQR: 13.0–42.1), while the rural and urban residents had significantly lower (p<0.001) levels of 11.3 μg/g creatinine (IQR: 5.3–18.7) and 11.9 μg/g creatinine (IQR: 6.3–20.3), respectively. In sprayers who had recently applied an OP pesticide (n=28), the median levels of DAP metabolites were 31.8 μg/g creatinine (IQR: 22.3–117.2). Logistic regression analysis showed that the use of full body coveralls while handling and spraying pesticides was significantly associated with lower DAP levels (OR 4.05, 95% CI 1.22 to 13.46). Also, changing clothes immediately after accidental contamination of clothing with pesticide amounts was found to be significantly associated with lower exposure levels (OR 4.04, CI 1.05 to 15.57). Conclusions: Our study findings confirm the increased exposure to OPs in pesticide sprayers and underline the importance of protective measures especially those that focus on dermal exposure mitigation.